Problems Faced by Farm Women in Managing Enterprises - T. Sarah Kamala,; K. Atchuta Raju, (Journal of Agricultural Extension Management, 2025)
The contribution of women in the family and to the national economy has been grossly under estimated and even unrecognised. The Human Development Report (UNDP, 1995) revealsd that women's economic contributions are undervalued to the tune of US$ 11 trillion a year internationally. Sen (1987) argues that the perceived contribution of women as perceived by both men and women is often lower than their 'actual contribution' on account of social norms, the form and nature of work and the perception of legitimacy. In both rural and urban areas of developing countries, women are important contributors to the economic support of their households. Data from man y countries show that the poorer the households, the more the women work for income, and the larger the proportion of household income derived from women's earnings. In some landless households in India, for instance, women are often the major or even the sole income earners in their households (Agarwal, 1988). The rise in the number of households supported solely by women is an important variable explaining the 'feminisation of poverty' among rural poor